Usability testing of a 3D touch screen kiosk system for way-finding. - Tüzün, Hakan; Telli, Esra; Alır, Arman (Computers in Human Behavior, 2016)
This study aimed to determine the usability of a 3D touch screen kiosk system for way-finding at a shopping mall in Ankara, Turkey. The usability testing was conducted in collaboration with 15 authentic users and the usability problems were determined by giving authentic tasks to them. The data were collected using a usability testing form. The participants were given six authentic tasks and asked to complete them using the kiosk. The data were analyzed using descriptive statistical methods, content analysis, and the Mann-Whitney U Test. The tasks were completed with a high rate of success. There was no significant difference between the task durations of male and female participants. The main findings of the study show that prior experience using the kiosk and giving guidance during usage reduces the duration of the tasks, that there are certain problems with the touch screen and its 3D properties, participants' transfer of the types of interaction with which they are familiar to the kiosk experience leads them to make mistakes, and there are some usability problems related to the interface and content design. The results of this study and its suggestions about information and interface design can be used to design more usable kiosks.